Academic Stress, Self-Esteem and Non-Suicidal Self-Injury Behaviors among Hostelized Students - Yashra Mansoor; Dr. Shugafta Malik; Muhammad Waqas (Research Journal of Psychology, 2025)
The aim of this research was to explore the association between academic stress, self-esteem, and non-suicidal self-injury (NSSI) behaviors among hostelized students. For this study, a sample of N=300 (150 males and 150 females) was chosen using a purposive sampling technique from both public and private hostels in Faisalabad. Prior to responding to three standardized questionnaires, the Academic Stress Scale (ASS), the Rosenberg Self-Esteem Scale (RSE), and the Non-Suicidal Self-Injury Behaviors Scale (INS), the participants filled out demographic form and gave their informed consent. Analysis of the data indicates that NSSI behaviors and academic stress have positive correlation. In contrast, Academic Stress was found to have a negative relationship with Self-Esteem, suggesting that as stress increases, self-esteem tends to decrease. Additionally, the findings revealed that undergraduates report lower self-esteem and engage in NSSI behaviors more frequently than graduate students, highlighting developmental differences in how academic challenges impact mental health. This research emphasizes the need for targeted interventions to reduce academic stress and improve self-esteem among hostelized students to decrease the risk of NSSI.